Text as the material basis of polymodal exercises in a non-linguistic university - Kirillovykh, Alexandra A. (Вестник Томского государственного университета)
Communicative-cognitive and polymodal approaches standpoint is used to examine professional texts as material means of polymodal exercises and to determine their significant characteristics, selection principles, and organization principles for elementary foreign language education in a non-linguistic university. The theoretical, empirical, and statistical methods were used to conduct the study and develop professional text typology considering current situation in the educational environment.